Music and emotions - Piotr Przybysz (Avant, 2013)
This paper discusses contemporary empirical approaches to the topic of music and emotions that are conducted at the intersection of psychology, neuroscience and musicology. I show that within this interdisciplinary programme a number of general issues were posed that are not that distant from the questions asked by the classical authors such as Stravinsky and Hanslick. The main purpose of the paper is to show that there are three areas of cognitive and behavioural activity of the listener and the respective types of musical emotions: embodied emotions, cognitive emotions, as well as associative and contextual emotions.